Factors contributing to innovation orientation of Singapore technology small and medium enterprises (SMEs) - NEO, Kok Beng (Institutional Knowledge at Singapore Management University, 2021)
As Singapore transitioned from economy that was primarily dependent on foreign direct investments (FDI) to a knowledge-based economy driven by indigenously developed science, technology and innovations, it became critical for the local firms to grow and internationalize. The government has thus invested heavily (of $19 billion from 2016 to 2020, and $25 billion from 2021 to 2015) in science and technology research and development. The Committee of Future Economy (CFE) concluded that in an era of rapid technological change where innovation cycles have shortened, one of economic strategy is to support our “high growth” enterprises to “scale up”. However, the inherent constraints and geographical limitations of Singapore means that domestic market will not be able to support “large enterprises” compared to larger economies. To do so, firms need to innovate. The Singapore government has encouraged technology-based small and medium-sized enterprises (SMEs) to enter overseas market through innovative products and services. However, little is known about the factors that these SMEs should inculcate in order to be innovative; what is needed for innovation orientation that has been found to be essential for innovations in SMEs. Innovation Orientation is a theoretical concept that describes the various factors of an innovative organizations that resulted in pro-active growth. Current literature and research in Innovation Orientation is largely based on established organization and from the perspective of USA and Europe. There is a research gap for countries with small domestic market and based in Asia. This research aims to fill this gap for Singapore technology-based SMEs. Using the case-study approach, 7 selected companies with high growth and global mindset were selected through semi-structured interviews. Such purposive criteria allow the identification of critical factors that contributed to the successful entry of Singapore Technology SMEs into overseas markets. Through this research, we contribute to existing literature where the internal factors leading to a firms’ Innovation Orientation are clearly delineated and applied through the Innovation Culture and Innovation Constructs. We also discovered that, in addition to the internal factors that make for innovation orientation, there are external factors driven by government policy that featured in the cases. These findings provide pointers for policy makers on the various programmes, initiatives and instruments that are desired to successfully facilitate the Innovation Orientation of SMEs.